ADOPTION OF TRADITIONAL AND DIGITAL MARKETING COMMUNICATION MEDIA IN THE TWENTY-FIRST CENTURY: A CONCEPTUAL ANALYSIS - Bassey, Agnes Edem (African Journal of Social and Behavioural Sciences, 2025)
The study examines the adoption of traditional and digital marketing communication media in the 21st century through a conceptual analysis of 15 peer-reviewed journal articles from three online portals (Google Scholar, Research Gate, and Semantic Scholars). Exploratory research design was adopted, and secondary data were gathered from extant literature and online journal articles published on traditional and digital marketing communication media acceptance from 2011 to 2023, as well as peer-reviewed journals written in English and available in full text. The inclusion-exclusion criteria aided this process with the help of a critical appraisal skill programme (CASP). Findings indicate media acceptance rates of 45 percent (traditional), 52 percent (digital), and 3.4 percent (hybrid), respectively. The study concludes with recommendations for a 360-degree marketing strategy to optimize effectiveness in a complex media environment.